Assessment of information as regards the toxicity of T‐2 and HT‐2 toxin for ruminants. (30th September 2022) - ,; Schrenk, Dieter; Bignami, Margherita; Bodin, Laurent; Chipman, James Kevin; del Mazo, Jesús; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Leblanc, Jean‐Charles; Nielsen, Elsa; Ntzani, Evangelia; Petersen, Annette; et al.
Abstract: In 2011, the EFSA Panel on Contaminants in the Food Chain (CONTAM) adopted a Scientific Opinion on the risks for animal health related to the presence of T‐2 (T2) and HT‐2 (HT2) toxin in food and feed. No observed adverse effect levels (NOAELs) and lowest observed adverse effect levels (LOAELs) were derived for different animal species. In ruminants a LOAEL was established for the sum of T2 and HT2 of 0.3 mg/kg body weight (bw) per day, based on studies with calves and lambs. The CONTAM Panel noted that the effects observed in nutritionally challenged heifers and ewes give rise to the assumption that rumen detoxification of T2 may not always be complete and therefore effective to prevent adverse effects in ruminants. However, the limited data on the effects of T2 on adult ruminants did not allow a conclusion. The European Commission requested EFSA to review the information regarding the toxicity of T2 and HT2 for ruminants and to revise, if necessary, the established Reference Point (RP). Adverse effect levels of 0.001 and 0.01 mg T2/kg bw per day for, respectively, sheep and cows, were derived from case studies, estimated to correspond to feed concentrations of 0.035 mg T2/kg for sheep and 0.6 mg T2/kg for cows. RPs for adverse animal health effects of 0.01 mg/kg feed for sheep and 0.2 mg/kg feed for cows were established. For goats, the RP for cows was selected, in the absence of data that they are more sensitive. Based on mean exposure estimates performed in the previous Opinion, the risk of adverse health effects of feeds containing T2 and HT2 was considered a concern for lactating sheep. For milking goats, a comparison performed between dietary exposure and the RP derived for cows, indicates a potential risk for adverse health effects. For dairy cows and fattening beef, the risk is considered low.